Haemochromatosis presenting as congestive cardiac failure. Issue 1 (January 1995) - Porter, J.; Cary, N.; Schofield, P.
Abstract : A 24 year old man with congestive cardiac failure was found to have grossly increased transferrin saturations, raised serum ferritin, and an iron-laden myocardium on biopsy. Initial treatment with the iron chelator desferrioxamine was replaced by weekly venesection. He was placed on the cardiac transplant list because of severe left ventricular dysfunction but was later removed because his symptoms and function improved. He remains well with few symptoms and is maintained on regular venesection and testosterone injections.